1993
DOI: 10.1042/bj2920343
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ferrochelatase mRNA in erythroid and non-erythroid cells

Abstract: Ferrochelatase, which catalyses the last step in haem biosynthesis, i.e. the insertion of Fe(II) into protophorphyrin IX, is present in all cells, but is particularly abundant in erythroid cells during haemoglobinization. Using mouse ferrochelatase cDNA as a probe two ferrochelatase transcripts, having lengths of 2.9 kb and 2.2 kb, were found in extracts of mouse liver, kidney, brain, muscle and spleen, the 2.9 kb transcript being more abundant in the non-erythroid tissues and the 2.2 kb transcript more predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Treatment of MEL cells with 2% DMSO induces rapid progression of MEL cells from a stage resembling late erythroid colonyforming units to a stage resembling basophilic and orthochromatophilic erythroblasts in the erythroid lineage, 35 where globin expression and hemoglobin formation are observed, along with increased expression of ferrochelatase mRNA and protein. 36 Treatment of differentiating MEL cells concomitantly with the iron chelator desferrioxamine (DFO) caused a sustained increase in IRE binding activity of IRP1 and IRP2 ( Figure 2B), whereas the differentiationinduced increase in activity of the [4Fe-4S] cluster-containing mitochondrial and cytosolic aconitases was attenuated ( Figure 2C), consistent with cellular iron depletion. Induction of Alas2 mRNA expression was observed during differentiation of MEL cells under both normal and iron-depleted conditions ( Figure 2D).…”
Section: Posttranscriptional Regulation Of Ferrochelatase In Mel Cellmentioning
confidence: 48%
“…Treatment of MEL cells with 2% DMSO induces rapid progression of MEL cells from a stage resembling late erythroid colonyforming units to a stage resembling basophilic and orthochromatophilic erythroblasts in the erythroid lineage, 35 where globin expression and hemoglobin formation are observed, along with increased expression of ferrochelatase mRNA and protein. 36 Treatment of differentiating MEL cells concomitantly with the iron chelator desferrioxamine (DFO) caused a sustained increase in IRE binding activity of IRP1 and IRP2 ( Figure 2B), whereas the differentiationinduced increase in activity of the [4Fe-4S] cluster-containing mitochondrial and cytosolic aconitases was attenuated ( Figure 2C), consistent with cellular iron depletion. Induction of Alas2 mRNA expression was observed during differentiation of MEL cells under both normal and iron-depleted conditions ( Figure 2D).…”
Section: Posttranscriptional Regulation Of Ferrochelatase In Mel Cellmentioning
confidence: 48%
“…A recent study reported successful KO of the ALAS and FC genes in the related rodent malaria parasite, P. berghei, but the authors were unable to show that these mutations ablated de novo heme synthesis (28), most likely due to background heme biosynthetic activity from the metabolically active host reticulocytes (29,30). This same study also revisited the effects of succinylacetone on the growth and heme biosynthesis activity of blood-stage P. falciparum.…”
Section: Discussionmentioning
confidence: 93%
“…Unlike P. falciparum, P. berghei parasites preferentially invade metabolically active reticulocytes, which also synthesize heme (29,30). Therefore, Nagaraj et al (28), who assessed heme biosynthesis by monitoring incorporation of [ 14 C]ALA into heme by autoradiography, were unable to show that de novo heme synthesis was disrupted in the knock-out parasites due to host cell background.…”
mentioning
confidence: 99%
“…When MEL cells are induced to differentiate with DMSO, the amounts of ferrochelatase mRNA increase 5-to 6-fold by 72 h, and the size of the mRNA in the differentiated MEL cell is the same as that in mouse liver [56]. There is a recent report by Chan et al [72] showing differential induction of the two FeC mRNA in MEL cells. Northern blot analysis of rat ferrochelatase mRNA reveals that the ferrochelatase mRNA in liver is shown to be a single 2.4 kb band, and that the amount of an mRNA of the same size markedly increases in the spleen of anemic rats (unpublished observation).…”
Section: Gene Structure and Expressionmentioning
confidence: 88%